Oral findings and salivary parameters in children with celiac disease: a preliminary study - Acar, Sibel; Yetkıner, Arzu Aykut; Ersın, Nazan; Oncag, Ozant; Aydogdu, Sema; Arıkan, Cigdem (Medical principles and practice, 2012)
The aim of this study was to investigate the prevalence of dental enamel defects, recurrent aphthous stomatitis (RAS) and caries experience and to measure salivary flow rate, buffer capacity, saliva and plaque pH and salivary cariogenic microflora in patients with celiac disease (CD) compared to healthy subjects. Thirty-five patients, aged 6-19 years, with a diagnosis of CD and 35 healthy children of the same age participated in the study. Enamel defects were diagnosed and classified using Aine's classification. The patients with RAS and dental caries were recorded using WHO criteria. The parents were interviewed about various oral health-related factors. Saliva samples were collected to measure the stimulated salivary flow rate, buffer capacity and pH values of saliva and plaque. Salivary mutans streptococci and lactobacilli were counted. The enamel defects and RAS prevalence were statistically higher (40 and 37.1%, respectively) in the CD group, and the prevalence of salivary mutans streptococci (48 and 14%) and lactobacilli (51 and 34%) colonization was statistically lower (p = 0.012, p = 0.010) in the CD group; the DMFS and dfs values were similar in both groups. CD appeared to be associated with a significantly higher prevalence of developing enamel defects and RAS, but a lower prevalence of salivary mutans streptococci and lactobacilli colonization, and the diagnosis of these oral manifestations might be helpful for an early diagnosis of CD.